Daily variation patterns in seagrass photosynthesis along a vertical gradient - Silva, João (2018)
The relationship between the available photosynthetic active radiation (PAR) and the photosynthetic yield of Photosystem II (PSII), measured by chlorophyll a fluorescence, was assessed in the intertidal seagrasses of Ria Formosa, a coastal lagoon in southern Portugal. Most of the lagoon's intertidal is occupied by a monospecific population of Zostera noltii (Hornemann), which occupies a vertical gradient of about 2 m. The upper distribution limit of this species comprises the edge of a Spartina maritima (Curtis) Fernald saltmarsh and the lower limit the transition to the subtidal, dominated by Cymodocea nodosa (Ucria) Ascherson. Diurnal changes in the pattern of rapid-light curves (RLCs) was investigated with pulse amplitude-modulated (PAM) fluorometry in Z. noltii and in C. nodosa in the upper and lower intertidal. The light reactions of photosynthesis were assessed by fitting photosynthesis-irradiance (P-I) models to the RLCs. The photosynthetic parameters of Z noltii revealed that this plant species exhibits sun- and shade-type responses in its upper and lower vertical distribution limits, respectively. At the lower distribution limit in low light, the initial slopes of all RLCs were significantly higher than at the upper site, but decreased with increasing irradiances, while at the upper distribution limit, although lower, the slopes were unaffected by increasing irradiance. C. nodosa presented a typical shade-type response, as evidenced by the daily variation and light dependence of both photosynthetic efficiency and optimal quantum yield. The relationship between the maximum electron-transport rate and irradiance suggests that this species is strongly light-limited. We suggest that attempts to characterize the photosynthetic behaviour of an intertidal meadow should consider both diurnal fluctuations in the plants' photosynthetic activity as well as its vertical distribution frequency.